QoS rerouting mechanism for SON - Long-fei WANG; Xing-wei WANG; Min HUANG (Tongxin xuebao)
Along with the development of computer network,SON(self-organizing network)has attracted wide attention with its flexibility,adaptability,robustness.On the basis of OSPFv3,the interactive message of QoS state was defined to establish the information table of neighbors,store the link QoS information,judge the triggering of rerouting,and then the biological behaviors,such as hibernation and awakening,were introduced to the routing nodes.A hybrid rerouting mechanism was adopted to make the corresponding treatment under various network failure situations,so that the application QoS support could be provided when the network state was changing.Simulation results show that the proposed mechanism has better performance.